GOLD-COPPER MINERALIZATION IN ALKALINE ROCKS - Muller D. (My University, 2002)
As part of the "Drosophila of igneous petrology" (Barker 1983), alkaline rocks have gained much attention among petrologists worldwide, mainly due to their distinct geochemistry, and many geoscientists still consider them as petrological curiosities with an obscure petrogenesis. In the past, a plethora of genetic hypotheses and a large number of local names for alkaline rocks from different localities have been created (see reviews by Sørensen 1974